The boys' war : Confederate and Union soldiers talk about the Civil War - Murphy, Jim, 1947- (New York : Clarion Books, 1990)
Includes diary entries, personal letters, and archival photographs to describe the experiences of boys, sixteen years old or younger, who fought in the Civil War.
Includes bibliographical references (p. 103-106) and index.
Keywords: United States. -- Army -- Recruiting, enlistment, etc. -- Civil War, 1861-1865 -- Juvenile literature; Confederate States of America. -- Army -- Recruiting, enlistment, etc. -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Personal narratives -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Children -- Juvenile literature; United States -- History -- Civil War, 1861-1865 -- Personal narratives; United States -- History -- Civil War, 1861-1865 -- Children